How much does experience matter in NCAA division I volleyball? A retrospective study - Bunn, J.; Schuitema, S.; Zhang, S.; Mayhew, J. (Research Quarterly for Exercise and Sport, 2019)
Purpose: To evaluate the relationship between years of collegiate playing experience and success of NCAA Division I volleyball programs. Methods: Data were gathered from the 2010-2015 seasons for each volleyball program in the "power five" conferences. Players that were involved in at least 66% of the sets were selected for analysis. Each player's years of college experience were tabulated and a team average experience score was created. This score was correlated with the end of season Ratings Percentage Index (RPI). Years with a significant correlation between success and experience were further analyzed for differences in on-court statistics by years of experience. Results: The range for team average experience score was 2.52-2.66. Only the 2012 season showed a moderate correlation between the team average score and RPI (rho = -0.421, p = .001), indicating that more experienced teams finished with a higher national ranking. Within this year, teams with more experience had a statistically significant (p < .05) higher season win percentage, higher conference win percentage, higher hitting percentage, more kills/set, and more assists/set than teams with low or only moderate experience. Conclusions: These data suggest that more collegiate playing experience does not always result in a significantly more successful season, but trends indicate that a relationship does exist between experience and success. In the one year that showed significance, more experienced teams had more favorable statistics related to skills that terminate play (e.g., kills) rather than ball control skills (e.g., digs and passing).